The World Bank’s Partnership with the GAVI Alliance - Independent Evaluation Group (World Bank, Washington, DC, 2016)
Global alliance for vaccines and immunization (GAVI) is the third largest multilateral in the health sector. It has a single-purpose mandate, to increase access to immunization in poor countries. The World Bank is a founding partner to GAVI and remains a major partner, particularly at a financial level by supporting operations of two major innovative financial mechanisms on its behalf. The Bank’s most significant contribution is a key role in the establishment and management of two innovative financing mechanisms (International Finance Facility for Immunisation (IFFIm) and Advanced Market Commitment (AMC)) that have contributed one-third of GAVI’s financial resources from 2000 to 2010. The relationship with GAVI has been collegial and constructive in countries where there is engagement, but in many countries the Bank is not substantially involved in immunization. This review concludes that the status quo leaves organizational synergies untapped, and that stronger Bank involvement, drawing on its strengths in sustainable funding for immunization, addressing inequities in access to immunization, investments in health systems strengthening, and donor coordination in health can help achieve greater development results.